Memproteksi Warung Kelontong Dari Ekspansi Minimarket Dan Revolusi Industri 4.0 - Abdul shomad (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2021)
Grocery stall are a sector of the populist economy. Now, its existence is increasingly marginalized by the massive invasion of minimarkets to the corners of the village. The revenues, arrivals of consumers and their profits have been eroded. Government regulation; Presidential Regulation (Perpres) No. 112 of 2007 concerning the Arrangement and Construction of Traditional Markets, Shopping Centers and Moderns Stores is not in a way to protect grocery stall. This research is a policy analysis conduced using a qualitative methodology. The data were processed triangulatively; form previous research data, the results of in-depth interviews with purposive sampling respondents who owned grocery stall in Bekasi Regency and Bekasi City and other literatures. Its results, basically the grocery stall owner understand the management of managing stalls, but do not have access to funding, politics and human resources. The regulations are not in favor of the grocery stall. Then, the grocery stall will not be able to ‘fight’ minimarkets without the intervention of the central and local governments. There needs to be a special regulation to protect this populist economy sector.